(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: This study aimed to identify the impact of the information technology governance on the quality of the financial reports in the Iraqi commercial banks: The modified role of cloud accounting and the need to activate the mechanisms of information technology governance to reduce the risks accompanying the use of the information technology Materials and Methods: For achieving the goals of the study, the researcher adopted the descriptive and analytical approach in addition to a questionnaire collected and analyzed by the (SPSS). The study sample consisted of (251) male and female employees in the information technology and accounting departments in the commercial banks. Conclusions: The study concluded that, a statistically significant impact at sig. (α≤0.05) for the information technology governance with its dimensions (planning and organizing, owning and implementing, support and delivery, follow-up and evaluation, direction and control) on the quality of the financial reports in the banks. The study also found a statistically significant impact at sig. (α≤0.05) for the cloud accounting as a modified variable on the relationship between information technology governance and the quality of financial reports in the banks, where the addition of the modified variable (cloud accounting) to the regression model. The study recommends that the departments in the commercial banks be interested in informing all the employees of their roles within the framework of the use of information technology in a clear and written manner.